State bodies’ role in protecting and ensuring of minor’s constitutional rights and freedoms - Abikenova, G.B.; Lavnichak, A. (KSU Publ., 2018)
The issue of guarantees for implementation and protection of minor’s rights and freedoms, is directly related to the theoretical and legal analysis of guarantees of human and citizen's rights. Rights and freedoms are a kind of basis on which the whole ramified system of legal opportunities is based, ensuring the complete realization by the individual their own interests. The protection of child`s rights is one of the most serious contemporary social problems caused by the violation of the rights of this category of population in recent years, as well as the lack of effective mechanisms for protecting and restoring the violated rights of minor’s, and imperfect legislation in this sphere.Meanwhile, the UN Convention on the Rights of the Child, the main international document regulating the rights of children, covers for the state obligation to provide the child with the protection necessary for his well-being and to take all appropriate legislative and administrative measures for this. The powers and main directions of the activity of state bodies in protecting and ensuring the constitutional rights and freedoms of minors are analyzed in the article. The review of the national legislation in the sphere of realization of the rights and freedoms of minor’s was conducted. The article says that a wide range of state bodies that are guarantors of ensuring the rights and freedoms of minor’s has proved its effectiveness in the implementation of the legal rights and freedoms of minor’s, its relevance to society and authorities.
Kəмелетке толмағандардың конституциялық құқықтары мен бостандақтарын қорғау жəне қамтамасыз етудегі мемлекеттік органдардың рөлі
Роль государственных органов в защите и обеспечении конституционных прав и свобод несовершеннолетних
Keywords: guarantees for the realization of the rights and freedoms of minors; protection of the rights of minor’s; ombudsman for the rights of the child; presidential control; government control; judicial control; constitutional control